Experimental and numerical investigation on the ballistic resistance of 2024-T351 aluminum alloy plates with various thicknesses struck by blunt projectiles. (May 2022) - Han, Jue; Shi, Yahui; Ma, Qianqian; Vershinin, Vladislav V.; Chen, Xiaozhen; Xiao, Xinke; Jia, Bin
Highlights: Ballistic impact behavior of 2024-T351 aluminum alloy plates with various thicknesses against blunt projectiles was investigated. With an increase in target thickness, the ballistic resistance improves but the increasing rate slows down gradually. At impact velocities slightly below the BLVs, fracture initiates at the rear surface of the target and propagates to the impact side for 2 mm thick target, while cracks are observed both at the corner of the indention and the rear surface of the plates for targets of 4 mm or thicker. Numerical simulations using MMC fracture criterion correlate well with experiments in terms of BLVs, fracture path and the effect of target thickness on BLVs. The deviation of the predicted BLVs of 2, 4, 4.82, 8 and 9.94 mm thick targets from the corresponding experimental values is 12.3%, 0.1%, 0.0%, 4.2% and 4.9%, respectively. MJC fracture criterion overpredicts the ballistic resistance of targets with increasing thickness. The deviation of the predicted BLVs of 2, 4, 4.82, 8 and 9.94 mm thick targets is 9.0%, 17.5%, 21.5%, 24.2% and 26.3%, respectively. Abstract: As one of the most commonly used aerospace aluminum alloys, 2024-T351 aluminum alloy plates are frequently exposed to impact loadings. In this study, the ballistic resistance of 2, 4, 4.82 and 8 mm thick 2024-T351 aluminum alloy plates struck by blunt projectiles was investigated both experimentally and numerically. Ballistic impact tests of 2024-T351 aluminum alloy plates of different thicknesses were carried out using a one-stage gas gun, and the initial-residual velocities and the ballistic curves were determined experimentally. It was found that the plates failed by shear plugging regardless of target thickness and the enhancement of ballistic limit velocity decreased with an increase in the target thickness. In parallel with experiments, numerical simulations were carried out by ABAQUS/Explicit. Deformation behavior of the plates was described by a modified Johnson-Cook (MJC) plasticity model accompanied with either the Lode-dependent modified Mohr-Coulomb (MMC) fracture criterion or the Lode-independent modified Johnson-Cook (MJC) fracture criterion (MJC). Numerical simulations showed that the ballistic limit velocities and the fracture path predicted by the Lode-dependent MMC fracture criterion were in better agreement with the experimental ones. Detailed analysis on the fracture path was performed and it was found that the normalized Lode angle was close to zero while the stress triaxiality was negative except for the 2 mm thick targets. Within such a stress state region, the Lode independent MJC fracture criterion obviously overpredicted ductility of the material and thus predicted much higher ballistic limit velocities. The main objective of the study is to reveal the necessity of incorporating Lode angle into a fracture criterion in predicting ballistic resistance of 2024-T351 aluminum alloy plates with various thicknesses struck by blunt projectiles through finite element (FE) simulations.